Energy transfer along Müller cell intermediate filaments isolated from porcine retina: II. Excitons at 2500 cm−1 produced by ADH1A upon hydrolysis of one ATP molecule - Khmelinskii, Igor (2021)
Low-energy (IR -2500 cm-1) exciton transfer was explored in Muller cell (MC) intermediate filaments (IFs) isolated from porcine retina and filling a capillary matrix. IR excitons were generated either by absorption of IR radiation at 4 mu m, or by ATP hydrolysis energy transfer to the MC IFs. ATP hydrolysis was catalyzed by human alcohol dehydrogenase (ADH1A) in ADH1A...NAD+...IF complexes. Each exciton was generated by hydrolysis of one ATP molecule. Exciton energy was independent on ATP concentration. The emission spectra of IR excitons arriving to the other side of the capillary matrix were dependent on the exciton generation method. Timeresolved experiments with direct exciton generation by pulsed IR radiation allowed to measure exciton travel velocity, along with the exciton emission time. The results obtained support new ideas on ATP energy transfer along protein filaments in vivo. These unique experimental results provide for detailed understanding of the electronic state structure of the MC IFs. This study reports that MC IFs isolated from porcine retina have a longliving low-lying electronic excited state at 2500 cm-1 above the ground state.